2009
DOI: 10.1038/sj.bjc.6605212
|View full text |Cite
|
Sign up to set email alerts
|

Expression of activated signal transducer and activator of transcription-3 predicts poor prognosis in cervical squamous-cell carcinoma

Abstract: Background:Stat3 is a member of the Janus-activated kinase/STAT signalling pathway. It normally resides in the cytoplasm and can be activated through phosphorylation. Activated Stat3 (p-Stat3) translocates to the nucleus to activate the transcription of several molecules involved in cell survival and proliferation. The constitutive activation of Stat3 has been shown in various types of malignancies, and its expression has been reported to indicate a poor prognosis. However, the correlation between the constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 33 publications
3
72
0
2
Order By: Relevance
“…Positive staining was mostly confined to the tumor borders adjacent to the stroma, suggesting a paracrine mode of STAT3 activation. In line with our results, another study found pTyr705-STAT3 in less than 10% of cells in most cervical cancer cases (34) and two previous studies detected pTyr705-STAT3 (35) or stronger nuclear STAT3 staining (36,37) in 22%-24% of cervical cancers. Only one group detected higher percentages of STAT3-phosphorylation in cervical cancers in an Indian population (38).…”
Section: Discussionsupporting
confidence: 80%
“…Positive staining was mostly confined to the tumor borders adjacent to the stroma, suggesting a paracrine mode of STAT3 activation. In line with our results, another study found pTyr705-STAT3 in less than 10% of cells in most cervical cancer cases (34) and two previous studies detected pTyr705-STAT3 (35) or stronger nuclear STAT3 staining (36,37) in 22%-24% of cervical cancers. Only one group detected higher percentages of STAT3-phosphorylation in cervical cancers in an Indian population (38).…”
Section: Discussionsupporting
confidence: 80%
“…STATs represent central regulators of cancer-associated inflammation and influence interactions between cancer cells and their immune microenvironment that determine whether the inflammation promotes or inhibits cancer. The majority of gynecologic tumors have high STAT3 activity and this was associated with poor survival and chemoresistance (40). Interestingly, it has been reported that COX-2 is a transcriptional target of STAT3 signaling (41).…”
Section: Discussionmentioning
confidence: 99%
“…As an important member of the STAT protein family, STAT3 participates in tumor cell survival, proliferation, migration, invasion, angiogenesis, and inhibition of apoptosis 12,13 in many types of human cancer, including lung cancer. [14][15][16][17][18][19][20][21] Moreover, the association between single nucleotide polymorphisms (SNPs) of STAT3 and susceptibility to carcinogenesis has been confirmed. 22,23 Additionally, it has been recognized that increased expression of STAT3 correlates with tumor progression and invasiveness; however, the causal mechanism of this molecular alteration and its prognostic value still remain unclear.…”
mentioning
confidence: 99%